Implementasi Sistem Among dalam Proses Pendidikan - Amiruddin, Amiruddin; Lubis, Bunga Br; Suryani, Mely; Masrura, Rizhani; Supardi, Supardi (MODELING: Jurnal Program Studi PGMI, 2023)
The purpose of this study is to thoroughly describe the Among System in the educational process. The among system is a way of educating children on the basis of independence and freedom so that students can grow according to their personal nature. The among system should be used as a way of educating to create an independent spirit so as to make students more courageous in learning what they want. The research design used is quantitative research which uses research journals and books related to the implementation of the among system in the educational process.